Communication Behavior of Farmers in Chatra District of Jharkhand (Indian Journal of Extension Education, 2020)
Effective communication from different source and channels are the essence of extension which provides agricultural information and knowledge to the farmers. A study was conducted on the communication behavior of farmers in Chatra district of Jharkhand in two blocks namely Prtappur and Gidhour selected randomly. Four villages selected purposively from these blocks and a total of 200 farmers were selected randomly from these 4 selected villages. Data collected through personal interview, group meeting, and structured schedule showed that among wall writing (51%) in mass communication Krishak Mitra (81%) in individual communication and Mobile message (81%) in group communication were the important sources available in a farmer’s field situation. It was found that majority of the farmers used wall writing, progressive farmers, and mobile message for accessing information. It was also found that KVK scientist was the most credible source of information followed by FLDs conducted by KVK scientist.